Characteristics of Korean students advised to seek psychiatric treatment before death by suicide - Kim, Hee Jin; Kweon, Yong-Sil; Hong, Hyun Ju (Frontiers in Psychiatry, 2022)
Introduction: Suicide is the leading cause of death among adolescents in Korea. Psychiatric disorders are well-known risk factors for suicide, but the proportion of children and adolescents who died by suicide and who had received psychiatric treatment is low. This study aims to examine how many school students who died by suicide were advised by their school to seek psychiatric treatment before their death and to characterize their clinical characteristics. Methods: We analyzed data collected by the Ministry of Education of Korea for all students who died by suicide between 2016 and 2020. Students were grouped according to whether or not they were advised to seek psychiatric treatment by their school-based on mental health screening and teachers’ judgements. Sociodemographic characteristics (sex, educational stage, family structure, socioeconomic status), suicide-related characteristics (place of suicide, suicide method, suicide note, previous self-harm, previous suicide attempt), emotional and behavioral status, school life and personal and family problems were compared between the two groups. Results: Analysis was conducted for 544 students, 110 (20.2%) of whom were advised to seek psychiatric treatment by their school before their death. This group had a higher proportion of girls; poorer attendance; higher frequency of depression, anxiety, impulsivity, and social problems; personal problems (appearance, friend-related, mental and physical health problems); family problems (mental health problems of family, bad relationship with parents, conflict of parents); and higher incidence of self-harm or suicide attempts (P< 0.001) than the other group. Conclusion: Teachers seem to advise psychiatric treatment when mental health problems are revealed at school. It showed distinctive clinical characteristics between the two groups. Preventing suicide among students requires the attention and effort not only of schools, but also of families, communities, and mental health professionals.